Industry at the cross-roads : productivity growth in the Windward Islands banana industry. - ANTOINE, Patrick (1997)
Traces the productivity performance of the Windward Islands banana industry, and identifies the major resources of industry growth over the period 1971-1994. Stresses the need for more emphasis to be placed on policy formulation and monitoring of industry performance.